Effects of the Glutamine Administration on T Helper Cell Regulation and Inflammatory Response in Obese Mice Complicated with Polymicrobial Sepsis - Chiu-Li Yeh; Li-Han Su; Jin-Ming Wu; Po-Jen Yang; Po-Chu Lee; Po-Da Chen; Chun-Chieh Huang; Der-Yirng Hsieh; Hsueh-Ju Wang; Sung-Ling Yeh; Ming-Tsan Lin (Hindawi Limited, 2020)
This study investigated the impacts of GLN on inflammation and T cell dysregulation in obese mice complicated with sepsis. Mice were divided into normal control (NC) and high-fat diet groups. The high-fat diet provided 60% of energy from fat and was administered for 10 weeks to induce obesity. Mice fed with a high-fat diet were then assigned to sham (SH) and sepsis with saline (SS) or GLN (SG) groups. The SH group was subjected to laparotomy, while the sepsis group underwent cecal ligation and puncture (CLP). The SS group was intravenously injected with saline. The SG group was intravenously administered GLN after CLP. Mice were sacrificed at 12, 24, or 48 h post-CLP, respectively. Results demonstrated that in the presence of obesity, sepsis drove CD4+ T cells toward the helper T (Th)2 and Th17 lineages. Also, expressions of inflammatory cytokines and macrophage infiltration markers in adipose tissues and lungs were elevated. Treatment of obese mice with GLN after sepsis reversed Th polarization and downregulated macrophage infiltration and inflammatory cytokine, whereas the tight junction-associated protein expression increased in the lungs. These findings suggest that the intravenous administration of GLN to obese mice after sepsis modulated a more balanced Th cell lineage, alleviated inflammation, and attenuated lung injury.